The Role of Guidance and Counseling Teachers in Developing Student Potential - Dwiyono, Erwin; Eliasa, Eva Imania (Manunggal Halim Jaya, 2025)
This writing research aims to understand the Role of Guidance and Counseling Teachers in developing student potential. The method in this writing uses the library research method or literature study as the main approach. This method includes collecting and analyzing data from various relevant written sources, including books, journals, scientific articles, and other documents related to the role of teachers in developing student potential. By using this library research method, the researcher conducted a systematic review and identification of journals which in each process followed the steps that had been set. The data analysis techniques used were clarifying, concluding, and concluding. The results of this journal writing research are: 1) Student Potential Development Strategy and 2 Guidance and Counseling Teachers' Efforts to Improve Students' Academic Achievement.